A novel double visible light active Z-scheme AgI/Ag/I-(BiO)2CO3 composite: Automatic formation of Ag bridge in the photocatalytic process. (October 2017) - Liang, Lei; Cao, Jing; Lin, Haili; Zhang, Meiyu; Guo, Xiaomin; Chen, Shifu
Graphical abstract: Highlights: Novel AgI/Ag/I-(BiO)2 CO3 hybrid composite was firstly constructed. AgI/Ag/I-(BiO)2 CO3 displayed excellent activity for RhB removal. Doping and heterojunction interface showed synergetic effects. Z-scheme mechanism of photocharge separation was proposed. Abstract: A novel Z-scheme AgI/Ag/I-(BiO)2 CO3 composite was constructed through a two step in-situ transforming process. AgI nanoparticles were firstly generated on the surface of I-(BiO)2 CO3 via ion-exchange step and then metallic Ag was formed by decomposing tiny of AgI in the photocatalytic process. Under visible light (λ > 400 nm), the as-prepared AgI/Ag/I-(BiO)2 CO3 composite intensively enhanced activity for rhodamine B degradation with corresponding k app value 0.63 h −1 in comparison with the reference samples. By means of the metallic Ag bridge, AgI/Ag/I-(BiO)2 CO3 displayed excellent separation efficiency of photocharges on the basis of a Z-scheme mechanism. Moreover, AgI/Ag/I-(BiO)2 CO3 kept good stability under visible light. This study provides a universal way to in-situ construct highly efficient Z-scheme (BiO)2 CO3 -based photocatalytic system applied for eliminating contaminants in wastewater.